Eksperimentasi Pembelajaran Bahasa Arab Menggunakan Media Gambar Pada Kelas X untuk Meningkatkan Penguasaan Mufrad?t - Rahmaya Unting Sari; Eka Utari Handayani (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2019)
The background of this study is the lack of creativity of teachers in using media in learning Arabic at MAN 3 Bantul, Yogyakarta. This study aims to determine the learning process of mufradât with picture media and find out the differences in learning outcomes of students in learning mufradât between experimental classes that use image media and control classes that do not use image media. This research is quantitative research and the type of research is experiment. Data collection is done by the method of testing, observation, and documentation. This experimental research was conducted with a pretest, posttest control group design model. The object used is class X IPS 1 as an experimental class and class X IPS 2 as a control class. While the data analysis technique uses independent samples t-test. The results of this study indicate that, there are significant differences between the experimental class and the control class. This difference can be seen from the average value of the control class posttest 66.312 while the posttest value of the experimental class is 90.125. Whereas the